2013
DOI: 10.2172/1086824
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Database of Liquid Salt Thermophysical

Abstract: The purpose of this report is to provide a review of thermophysical properties and thermochemical characteristics of candidate molten salt coolants, which may be used as a primary coolant within a nuclear reactor or heat transport medium from the Very High Temperature Reactor (VHTR) to a processing plant; for example, a hydrogen-production plant. Thermodynamic properties of four types of molten salts, including LiF-BeF 2 (67 and 33 mol%, respectively; also known as FLiBe), LiF-NaF-KF (46.5, 11.5, and 52 mol%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Chromia-forming alloys, Fe-based and Ni-based, do not show corrosion resistance in molten chlorides. It has been reported that increasing Cr content in those alloys produced an increase in corrosion rates whereas changes in nickel content showed no effect [112].…”
Section: High-temperature Molten Saltsmentioning
confidence: 95%
“…Chromia-forming alloys, Fe-based and Ni-based, do not show corrosion resistance in molten chlorides. It has been reported that increasing Cr content in those alloys produced an increase in corrosion rates whereas changes in nickel content showed no effect [112].…”
Section: High-temperature Molten Saltsmentioning
confidence: 95%